A record of changes in the Gran Sasso groundwater before, during and after the 2016 Amatrice earthquake, central Italy - De Luca, Gaetano (Sci Rep, 2018)
We performed continuous recordings (May 2015 – January 2017) of hydraulic pressure and electrical conductivity of groundwater in the 190 m-long horizontal S13 borehole drilled next to the deep underground laboratories of Gran Sasso (LNGS-INFN), located in the core of the Gran Sasso carbonate aquifer (central Italy) at a distance of about 39 km south-eastward from the 24 August 2016 Amatrice earthquake (6.0 M(w)) epicenter. Using a 3-channel, 24-bit ADC we achieved a sampling rate of groundwater physical properties up to 50 Hz for each channel. We focused on the analysis of data recorded before, during and after the Amatrice earthquake, describing and discussing in detail the evidence for significant hydraulic pressure and electrical conductivity anomalies recorded before the main shock. We identified unambiguous signals in the hydraulic pressure data starting on 19 August, i.e. five days before the 24 August mainshock. A more careful analysis allowed us to detect the inception of a weak change up to 40 days before the Amatrice earthquake and a significant variation in the electrical conductivity data about 60 days before. The data revealed highly dynamic aquifer behaviour associated with the uprising of geogas probably related to the preparation stage of the Amatrice earthquake.